Alienation and Nostalgia: A Diasporic Reading in The Little Buddha in Tokyo (American Journal of Arts and Human Science, 2024)
The main aim of this paper is to explore ‘alienation’ and ‘nostalgia’ as diasporic features in the story The Little Buddha in Tokyo by Parashu Pradhan. The protagonist Palden falls in love with a Japanese tourist girl in Kathmandu. They get married and fly to Tokyo in Japan. In the hostland, Palden’s discomfort begins as he is confined to the house of his wife Silvia Sann. He is not allowed to go out and work. His dream of earning a lot of money and having a happy life in Kathmandu, his homeland, faces a big problem. He feels alienated totally. He becomes nostalgic for his home, families, and homeland landscape in Nepal. Palden stands as a diasporic character in the story. This is a qualitative research. It implements the theories of ‘alienation’ and ‘nostalgia’ in ‘diaspora’ introduced by Fernando Galvan, Mahinder Kumar, Wayne O’Donohne and Lindsay Nelson, Karl Marx, Scott T. Allison and Jeffrey David Green and so on. It applies APA 7th edition as the research format. We have consulted library books, journal articles, magazine articles, and internet sources for e-journals and e-books reading related to the concepts ‘alienation’ and ‘nostalgia’ in connection with ‘diaspora.’ So, we, as researchers study how Palden faces ‘alienation’ and ‘nostalgia’ and becomes a diaspora in Japan, the host land. The certain lines from the story contain the protagonist’s experiences of ‘alienation’ and ‘nostalgia’ and they are analyzed as diasporic features to interpret him as a diasporic character. He is a Nepali diaspora in Japan. This paper will be a support to other prospective researchers in diaspora area.